Choosing between the Truth and Participants' Rights: The Dilemma of a Qualitative Researcher - Hussien, Suhailah (2019)
Making group work works in a classroom can be challenging, not only in the attainment of the objectives or results of the group work, but also of the whole process. This phenomenological study on the use of group work among pre-service teachers was initially aimed at exploring their experiences and understanding of group work as a process of learning and teaching. The study involved twelve final year female students enrolled in an undergraduate skill-based course. The students were given the task of organizing a field trip to an orphanage. They were provided with guidelines in planning and managing the trip, after which they were required to write a report. Students also documented their experience in a journal. Students’ reports and journals were analysed, and resulted in three broad themes, which were group work as a constructive pedagogy, as a process of development or learning, and the challenges of group work in terms of group dynamics. However, the third theme, which is, the intra and inter group relations and interactions, put the researcher in a situation where she found herself in a dilemma to present either the truth of the study (i.e. the results), or to maintain the rights of the participants. This paper discusses how the researcher managed her dilemma through the negotiation of her roles as a researcher and course instructor. At the same time, she was compelled to redefine the boundaries of the study with the participants’ consent. The paper reveals that a researcher’s readiness to return to the field and to the participants is imperative in our attempt to ensure that the ethical issues of a research are carefully attended to.